2020
DOI: 10.1155/2020/6953594
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer Montmorillonite Modified Fly Ash Ecological Slope Protection Material and Its Preparation and Application

Abstract: In order to scientifically and reasonably evaluate and select the quality and effect of ecological slope protection construction project and the structural form of ecological slope protection, this paper mainly studies nanomontmorillonite modified fly ash ecological slope protection material and its preparation method and related applications. The nanomontmorillonite modified fly ash ecological slope protection material and its application in this paper are based on nanomontmorillonite modified fly ash as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…It is demonstrated that the roots can improve soil shear resistance (Schwarz et al, 2010;Naghdi et al, 2013;Kokutse et al, 2016), and the water content of the soil with roots and length density of roots can be utilized as indications of slope stability. (Osman and Barakbah, 2006;Lou et al, 2020). Wang et al (2020) conducted comparative experiments on the impacts of herbaceous plants on slope protection and slope stability analyses in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that the roots can improve soil shear resistance (Schwarz et al, 2010;Naghdi et al, 2013;Kokutse et al, 2016), and the water content of the soil with roots and length density of roots can be utilized as indications of slope stability. (Osman and Barakbah, 2006;Lou et al, 2020). Wang et al (2020) conducted comparative experiments on the impacts of herbaceous plants on slope protection and slope stability analyses in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Natural disasters such as landslides and debris flows caused by slope instability are among the most frequent and harmful to human activities considering all kinds of geological disasters [1]. Rainfall is an important factor influencing slope instability [2], and slope ecological protection is a common form of slope protection [3,4], which is widely used in various projects such as highways, railroads and water conservancy [5,6]; however, the relationship between rainfall infiltration and ecological slope instability is still poorly understood. Therefore, it is important to study the rainfall infiltration and runoff rules of ecological slopes and determine the quantitative analysis model for ecological slope design.…”
Section: Introductionmentioning
confidence: 99%